PENGARUH KONSENTRASI MALTODEKSTRIN DAN SARI JERUK NIPIS TERHADAP TINGKAT KESUKAAN ORGANOLEPTIK MINUMAN INSTAN MENTIMUN (Cucumis sativus L.) - Zakiyah, Mei Dita Fitrotus; Budiandari, Rahmah Utami; Azara, Rima; Saidi, Ida Agustini (Jurnal Sagu, 2024)
Cucumber are fresh fruit that are commonly consumed, a source of vitamins and minerals, abundant production. Lime juice has a sour taste, high in vitamin C. Both agricultural product commodities have a short shelf life, so processing is required, namely instant powder drink using foam mat drying method. The purpose of this research to determine organoleptic characteristic od cucumber instan drink. This research used RBD  factorial, first factor was maltodextrin concentration (15%, 20%, 25%)and second factor was lime juice concentration (5%, 15%, 25%). Organoleptic characteristic used hedonic scale, data were analyzed used friedmen method. The  best result at 25% maltodextrin concentration and 25% lime juice concentration showed that colour organoleptic 3,47,  aroma organoleptic  3,37, texture organoleptic 3,57 and taste organoleptic 3,93